2019
DOI: 10.1038/s41598-019-40890-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry and Kinetics of the Thermal Degradation of 2-Methoxyethanol as Possible Biofuel Additives

Abstract: Oxygenated organic compounds derived from biomass (biofuel) are a promising alternative renewable energy resource. Alcohols are widely used as biofuels, but studies on bifunctional alcohols are still limited. This work investigates the unimolecular thermal degradation of 2-methoxyethanol (2ME) using DFT/BMK and ab initio (CBS-QB3 and G3) methods. Enthalpies of the formation of 2ME and its decomposition species have been calculated. Conventional transition state theory has been used to estimate the rate constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…The increased cytotoxicity of Samples 2 and 3 towards stem cells was most probably connected to the adsorption of the products of triethylene glycol oxidative thermolysis on the cerium oxide NPs’ surface. Despite the low toxicity of triethylene glycol itself [ 45 ], heating triethyleneglycol in air can produce various potentially toxic carbonyls and aldehydes [ 48 ]. Note that the higher toxicity of Sample 3 correlates well with the longer heating duration during its synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The increased cytotoxicity of Samples 2 and 3 towards stem cells was most probably connected to the adsorption of the products of triethylene glycol oxidative thermolysis on the cerium oxide NPs’ surface. Despite the low toxicity of triethylene glycol itself [ 45 ], heating triethyleneglycol in air can produce various potentially toxic carbonyls and aldehydes [ 48 ]. Note that the higher toxicity of Sample 3 correlates well with the longer heating duration during its synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Estimating BDEs can provide early insights into bond strength and fuel behavior at high ignition temperatures [ 89 , 90 , 91 , 92 , 93 ]. The CBS-QB3 energies were used to calculate the BDEs of the considered compounds at T = 298 K as depicted in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that computational method offers the most convenient path for studying structure-activity relationships in radical reactions to guide the design of novel antioxidants with enhanced activity [12][13][14][15][16][17][18][19]. In several prior studies, the radical scavenging activity of organic compounds in physiological environments was successfully evaluated by quantum chemistry calculations [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%